Nglurug Awig-Awig: Deviation Against Catur Brata Penyepian by Younger Generation on Nyepi Day Hindu Balinese in Lampung - Komang Danu Artha Arya Wiguna; Bartoven Vivit Nurdin; Ifaty Fadliliana Sari; Suwarno Suwarno; Syifaa Sabianova Addina Turki Turki; Mathis Corbin (Journal of Religion, Local Politics, and Law, 2026)
This study examines deviations from Catur Brata Penyepian during the Nyepi holiday among the Balinese Hindu community in Dharma Agung Mataram Village, Central Lampung, commonly referred to as nglurug awig awig. Catur Brata are the four main rules for observing Nyepi that should not be violated. However, in some cases, the younger generation still commits deviations. The Balinese community in Dharma Agung Mataram Village, Seputih Mataram District, Central Lampung, is Hindu and transmigrated to Lampung around 1963, bringing their religion and strong traditional customs with them. However, deviations against Catur Brata Penyepian still frequently occur. The theories used in this study are Hirschi's (1969) theory of social control and Lemert's (1951) theory of deviance. This study uses a qualitative research method, employing data collection techniques such as in-depth interviews, participant observation, and documentation. Data analysis is carried out through data reduction, data display, and data verification. The results of the study indicate two categories of violations committed by the younger generation: minor and serious. The causes of violations include a lack of religious understanding, economic pressures, the influence of modernity, weak socialization of the Catur Brata Penyepian, and lax supervision (lack of social control) in a relatively heterogeneous society. None of this can be categorized as social deviation or social pathology, but rather as a violation. The response from the community, traditional leaders, and Pecalang was generally disappointment, concern, and annoyance, with appropriate sanctions being imposed.